Application of pulsed electric fields to improve product yield and waste valorization in industrial tomato processing. (April 2020) - Andreou, Varvara; Dimopoulos, George; Dermesonlouoglou, Efimia; Taoukis, Petros
Abstract: The tomato processing industry strives to maximize product yield, keep energy costs and waste effluents to a minimum while maintaining high product quality. Pulsed Electric Field (PEF) processing increases plant cell permeability through electroporation and could be applied in tomato processing to facilitate peeling, increase juice yields and enhance valorization of tomato waste. PEF was applied to three different steps, of industrial tomato processing. In the first step, different PEF treatments (0.5–1.5 kV/cm, 0–8000 pulses, 15 μs pulse width) applied to whole tomatoes improved peeling, reducing the work required for peel detachment up to 72.3%. In the second step, PEF (0.5–2.5 kV/cm, 0–4000, pulses, 15 μs pulse width) applied to chopped tomatoes, increased tomato juice yield up to 20.5%. PEF was also applied to the residues of the first juicing step comprising seeds, peels and a fraction of tomato flesh, to further increase juice yield with the overall yield reaching 90.2%. In the third step the effects of PEF on the extraction of high added value compounds from juicing residues were studied. Carotenoid extraction yield increased up to 56.4%. Lycopene extraction increased from 9.84 mg lycopene/100 g to 14.31 mg/100 g tomato residue for a PEF treatment at 1.0 kV/cm for 7.5 ms. The concentration of extracted total phenolic compounds doubled (56.16 mg gallic acid/kg) with a 2 kV/cm, 700 pulses treatment. The increased antioxidant capacity was correlated to carotenoid concentration. Overall, targeted PEF pretreatments incorporated to industrial tomato processing lead to decreased energy demand and increased productivity. Highlights: PEF treatment led to decreased peel detachment work by 72.3%, without deteriorating the final firmness of the tomatoes. The highest tomato juice yield achieved was 20.5% higher compared to untreated sample after PEF processing. PEF at 5 kV/cm improved the carotenoid extraction (14.31 mg lycopene/100 g tomato waste) by 56.4%. The extraction of phenolic compounds doubled (56.16 mg GA/kg) for PEF conditions 2 kV/cm and 700 pulses from tomato waste. Cell disintegration index is a reliable measure which can be correlated with all aspects studied in the present work.